Natural Radioactivity and External Dose Assessment of Surface Soils in Bolikhamxay Province, Laos - Bui Van, Loat; Leuangtakoun, Somsavath; Kim Duyen, Vu Thi; Khang, Khong Nam (VNU Journal of Science: Mathematics - Physics, 2017)
We have determined activity concentrations in 33 soil samples collected from Bolikhamxay Province, Laos. The activity concentrations of the natural radionuclides 226 Ra, 232 Th and 40 K in soil samples were measured by a gamma spectrometer with a HPGe detector. The average activity concentrations of the natural radionuclides 226 Ra, 232 Th and 40 K are 43.8  ±  5.6, 57.0  ±  7.3 and 426.4  ±  23.1 Bq.kg -1 , respectively. The average activity concentrations of 226 Ra and 232 Th in this work are higher than those of the world average values. Meanwhile, the  activity concentration of 40 K is almost the same of the world average value. The estimated average outdoor annual effective dose (E) and radium equivalent actitvity (Ra eq ) are 0.17  ±  0.02 mSv.yr -1 and 154.8  ±  16.1 Bq.kg -1 , respectively.